The field trip book : study travel experiences in social studies - Morris, Ronald V. (Emerald Publishing Limited : Information Age Publishing, 2010)
Looking for social studies adventures to help students find connections to democratic citizenship? Look no further! The Field Trip Book: Study Travel Experiences in Social Studies provides just the answer teachers need for engaging students in field trips as researching learners with emphasis on interdisciplinary social studies plus skills in collecting and reporting data gathered from field explorations. This is the book for those educators who want to make social studies field experiences real and meaningful for their students.These real-world social studies experiences are teacher tested and focus on anthropology, civics, economics, geography, history, and sociology. The Field Trip Book: Study Travel Experiences in Social Studies makes social studies exciting for elementary and middle school students, by introducing them to content in the world around them. This book is perfect for the elementary or middle school teacher, museum educator, or parent looking forward to increasing interaction between students and learning sites.